Talent management practices a trajectory and ingenuity in higher education institutions: a meta-analysis review of literature - Miiro, Farooq; Othman, Azam (Springer, 2018)
The purpose of the article is to identify talent management practices in higher educational institutions. Meta-analysis literature review was undertaken in order to evaluate the role of talent management in successful attainment of institutional staff quality performance. Through literature review, it was found out that talent management has its share in modern organisational human resource management practices. The study revealed that human resource undoubtedly is an unpredictable resource with multi-coloured responses and attributes towards work; if these attributes are truly discovered, developed and utilised well, then they definitely have an added value on institutional total quality services. The paper also contended that there is a need to investigate its true practice currently embarked on in operations so as to find a suitable theory for the subject and its implication for organisational transformation and excellence.